2011
DOI: 10.1016/j.kjms.2011.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in patients undergoing cholecystectomy

Abstract: This large-scale prospective cohort study of a Taiwan population applied generalized estimating equations to evaluate predictors of health-related quality of life (HRQOL) after open cholecystectomy (OC) and laparoscopic cholecystectomy (LC) procedures performed between February 2007 and November 2008. The Gastrointestinal Quality of Life Index and Short Form-36 were used in a preoperative assessment and in 3(rd) month and 6(th) month postoperative assessments of 38 OC and 259 LC patients. The HRQOL of the chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(41 reference statements)
2
5
0
Order By: Relevance
“…Our study also concurs with findings of Hsueh et al (26) who concluded that the health related quality of life of the cholecystectomy patients were significantly improved at three months and six months after surgery (P < 0.05). Jaundice persisted in one patient in this group into postoperative period.…”
Section: Discussionsupporting
confidence: 93%
“…Our study also concurs with findings of Hsueh et al (26) who concluded that the health related quality of life of the cholecystectomy patients were significantly improved at three months and six months after surgery (P < 0.05). Jaundice persisted in one patient in this group into postoperative period.…”
Section: Discussionsupporting
confidence: 93%
“…The SF-36 questionnaire did not identify statistically significant differences between the study groups in general health perceptions, physical functioning, emotional well-being, social functioning, energy, body pain, and role functioning/emotional score. Only the role functioning/physical score was slightly higher in the LC group (P = 0.038) (12). These results are similar with that of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The present study has found an increasing risk of DD after cholecystectomy only in females, but not in males. One prior study suggests that female sex is significantly negatively associated with post-cholecystectomy health-related quality of life (HRQOL), as evaluated by the GIQLI and short Form-36 after a six-month follow-up [ 7 ]. Previous studies consistently report that PCS occurs frequently in women, while middle-aged women also have a high prevalence of DD [ 1 , 2 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its prevalence rate ranges from 10% to 15% in the United States and 3% to 10% for Asian countries [ 3 , 4 ]. Cholecystectomy is considered the curative intervention [ 5 7 ]. However, previous follow-up studies report that some residual gastrointestinal problems may continue to bother patients who had undergone cholecystectomy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%